Akuntansi Budaya dan Keberlanjutan Keuangan Berbasis Komunitas Dalam Upacara Adat Karo - Windasari, Ihsanul (JCA (Jurnal Cendekia Akuntansi), 2026)
This study aims to reveal the application of cultural accounting and its relation to community-based financial sustainability in the Karo traditional ceremony of the Tenggerese community. The ceremony is not only a religious ritual but also a sustainable community-based economic system emphasizing cooperation, transparency, trust, and cultural continuity. The financing process runs without formal accounting records, yet accountability is maintained through community participation in fund management. This research uses a qualitative approach with an ethnographic method involving interviews, observation, and document analysis. The results show that financing the Karo traditional ceremony is collective, where members contribute money, goods, or labor so no individual bears an economic burden. Community deliberation ensures transparency, with financial decisions discussed openly to prevent misuse. Collected funds are used for ceremonial needs and long-term goals such as temple maintenance, cultural education, and heritage preservation. The findings indicate that cultural accounting within the Tenggerese community embodies sustainability by integrating economic, social, and spiritual values to maintain traditions, strengthen solidarity, and preserve cultural identity amid modernization. Keywords: Cultural Accounting, Sustainability, Community-Based Finance, Accountability, Local Wisdom